Group Communication Strategy in Disseminating Information from the Medan City Communication and Information Service - Raudoh Sari Fatullah; Sori Monang (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
Citizens can access the information they need every day through the internet in today's information age. Individuals have been significantly affected by the emergence of web 2.0 technologies on the internet, especially the decentralization of information creation and distribution. This shows that anyone can create and disseminate knowledge online. When disseminating information from the Medan City Communication and Informatics Office, descriptive qualitative techniques are used in group communication strategies. Qualitative techniques can be considered as a way to conduct research that generates descriptive information about individuals or their behavior in the form of written or spoken words that can be compared with the context and the individual as a whole and used for analysis. The information dissemination strategy of the Medan City Communication and Informatics Service by evaluating their needs, implementing strategies through various counseling, understanding their situation, and providing feedback in a way that is understandable to the audience. To simplify the process of delivering messages, messages will be prepared, both through the pre-interaction stage and through the creation of information and message plans. The method will be decided through written and direct communication. Direct correspondence through the empowerment of officials to residents by utilizing communicated or communicated in language when conveying is recorded as hard copy as the medium used.